2013
DOI: 10.1007/s00211-013-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct and inverse computation of Jacobi matrices of infinite iterated function systems

Abstract: We introduce a new set of algorithms to compute the Jacobi matrices associated with invariant measures of infinite iterated function systems, composed of one–dimensional, homogeneous affine maps. We demonstrate their utility in the study of theoretical problems, like the conjectured almost periodicity of such Jacobi matrices, the singularity of the measures, and the logarithmic capacity of their support. Since our technique is based on a reversible transformation between pairs of Jacobi matrices, it can also b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Typically, it is found that the associated spectral measures are singular continuous, and in certain cases (like the so-called Fibonacci matrix [85,24]) supported on Cantor sets with self-similar geometry. Conversely, one can start with IFS balanced (not equilibrium) measures on such sets, and ask what are the properties of the associated Jacobi matrices-that can be computed numerically [31,56,65]. It is still an open problem to assess whether almost periodicity of some sort characterizes these matrices, as conjectured in [57].…”
Section: Background and Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, it is found that the associated spectral measures are singular continuous, and in certain cases (like the so-called Fibonacci matrix [85,24]) supported on Cantor sets with self-similar geometry. Conversely, one can start with IFS balanced (not equilibrium) measures on such sets, and ask what are the properties of the associated Jacobi matrices-that can be computed numerically [31,56,65]. It is still an open problem to assess whether almost periodicity of some sort characterizes these matrices, as conjectured in [57].…”
Section: Background and Motivationsmentioning
confidence: 99%
“…This provides a new algorithm for the difficult numerical problem of computing the Jacobi matrix J(µ). Since this latter can also be obtained by different, non iterative techniques [31,56,65], we can measure the convergence of the matrix entries of J(µ n ) as a function of the order n, to assess the relative performance the new algorithm.…”
Section: The Jacobi Matrix Of Balanced Ifs Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems possible to extend the proof in the original paper to the case of non-equal coefficients {α n }. Needless to say, this technique is classical in these problems [37,43,44].…”
Section: Existence and Regularity Resultsmentioning
confidence: 98%
“…A remarkable exception to this state of things is provided by the study of Bernoulli convolutions [26,41,44], where the main theoretical question to be answered is about the absolute continuity versus singularity of the invariant measure. A renewed interest in this question has been brought recently by the study of IFS with uncountably many maps [36,37]: preliminary results on a specific example show that a transition from singular behavior to absolute continuity and to increasing regularity of the density of an IFS measure takes place as a parameter is varied. Crucial for our aim, this density is a refinable function.…”
Section: Introductionmentioning
confidence: 98%